Evidence Base for Collaborating, Learning, and Adapting: summary of th e literature review (2016.08) - Lab, Learning (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Bas e for Collaborating, Learning, and Adapting (EB4CLA). The purpose of t his work is to answer key learning questions: